2014
DOI: 10.1186/preaccept-5624405321277583
|View full text |Cite
|
Sign up to set email alerts
|

dNTP pool modulation dynamics by SAMHD1 protein in monocyte-derived macrophages

Abstract: Background: SAMHD1 degrades deoxyribonucleotides (dNTPs), suppressing viral DNA synthesis in macrophages. Recently, viral protein X (Vpx) of HIV-2/SIVsm was shown to target SAMHD1 for proteosomal degradation and led to elevation of dNTP levels, which in turn accelerated proviral DNA synthesis of lentiviruses in macrophages. Results: We investigated both time-dependent and quantitative interplays between SAMHD1 level and dNTP concentrations during multiple exposures of Vpx in macrophages. The following were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 44 publications
2
21
1
Order By: Relevance
“…6B). However, these dNTP increases were much lower in magnitude and shorter in duration as compared to our data using VLPs (Hollenbaugh et al, 2014; Kim et al, 2012). Collectively, HIV-2 infected MDMs do not maintain high levels of dNTPs, since they are only needed during the reverse transcription and gap repair during viral DNA integration (Amie et al, 2013; Van Cor-Hosmer et al, 2013), which are very early events in the viral life cycle.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…6B). However, these dNTP increases were much lower in magnitude and shorter in duration as compared to our data using VLPs (Hollenbaugh et al, 2014; Kim et al, 2012). Collectively, HIV-2 infected MDMs do not maintain high levels of dNTPs, since they are only needed during the reverse transcription and gap repair during viral DNA integration (Amie et al, 2013; Van Cor-Hosmer et al, 2013), which are very early events in the viral life cycle.…”
Section: Discussioncontrasting
confidence: 96%
“…5E) remained relatively comparable without increasing from day 0. As expected, these data showed that Vpx in GL-AN virus containing Vpx promoted the increase in dNTPs, but this increase was much more transient in duration as compared to VLP treated MDMs (Hollenbaugh et al, 2014). Collectively, the importance of elevated dNTP concentration is most marked early after infection, when the majority of reverse transcription is thought to take place.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…SAMHD1 is widely established as a central regulator of dNTP pool dynamics within cells and as such its catalytic activity can directly influence the replicative capacity of the cell (97, 133136). Silencing or degradation of SAMHD1 results in elevated dNTP pools and altered growth kinetics as evidenced by studies that demonstrate an increased retention of cells in the G 1 phase with a corresponding loss in S-phase cells (97, 133, 137).…”
Section: Samhd1 Cellular Regulation and Nucleotide Metabolismmentioning
confidence: 99%